From Responsibility to Results: Measuring CSR’s Impact on Nepalese Corporate Success - Wagle, Sudip; Kukreja, Jyoti; Wijaya, Lianna; Subramanyam, Amit (Nepal Journal of Multidisciplinary Research, 2025)
Purpose: This study explored the relationship and influence of CSR initiatives on the corporate sector's performance in Nepal. CSR is considered to be both a causal marketing and a governance parameter thus ethical observance of its conduct is more often than not missing. The present research explores dimensions of commitment of funds, adherence to policies, framework of modus operandi and evaluation of the impact it created. Methods: This study used mix-methodology. The quantitative approach was deployed using published materials and a structured questionnaire was administered. Data was collected to procure real-time insights. Primary data collection for both the companies’ executives and the beneficiary institutions was then collated. Out of 162 questionnaires distributed, 127 usable questionnaires were returned from companies’ executives. Further, 400 questionnaires were recorded from the beneficiary institutions. Furthermore, the qualitative method was used: semi-structured interviews in personal face-to-face interactions were conducted. Representatives were selected from seven organizations that consented to participate. Results: The findings show that out of eight research queries, from two divisions: financial performances and strategic decisions, six have significantly confirmed the firm's positive performance. At the same time, customer and environmental relations appeared insignificant. Conclusion: This outcome confirms that the amount spent on CSR is poised to prove an investment instead of an expenditure. Subsequently, the beneficiary institution can derive satisfaction through various adaptation schemes such as building relations by solving the problems of the beneficiaries, which eventually leads to firm performance. Novelty: The results show divergence from previous findings, especially in the context of Nepal by accepting a noteworthy connection between the community and firm’s performance.